Peran Media Interaktif Dalam Meningkatkan Motivasi Belajar Siswa pada Mata Pelajaran SKI di Madrasah Ibtidaiyah - Munawir, Munawir; Rofiqoh, Ainur; Khairani, Ismi (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2024)
This research aims to describe the role of interactive teaching medias in increasing student’s motivation to learn in the Islamic Cultural History Subject. The results of this research were obtained by in-depth analysis of various relevant sources in the form of articles or other studies that are similar to the problem to be discussed. The History of Islamic Culture is one of the important subjects in the Islamic Religious Education curriculum as an effort to shape student character. As an important subject, the Cultural History Subject learning process must run well and should be fun, one of which can be achieved by choosing the right teaching medias. Along with the development of science and technology, teachers can use it to develop teaching medias according to their needs. Technology-oriented learning will make learning easier for students in receiving all information. The results of using interactive teaching medias in the form of animation videos, interactive game, and technology-based learning applications have been proven to be more effective and attracts more students' attention, so that it can foster learning motivation in students.Keywords - Interactive Teaching Material’s, Student’s Learning Motivation, SKI subject in Madrasah Ibtidaiyah.